PERANAN SERTIFIKASI HALAL BAGI KONSUMEN DALAM ASPEK PERLINDUNGAN KONSUMEN - Ester, Friska; Sandi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
Initiated from the drive of producing valued, high quality, and economicallyfeasible product, role of halal certification towards consumer remains important to beknown. This writing aims to illustrate the role of halal certification in the perspective ofconsumer protection. Method applied in this research shall be normative legal research,where it focuses the analysis of legal principles and the statutory laws. Awareness of theproducer to label the halal emblem shall be a prerequisite, due to the majority of thesociety are Moslems. It is also understood that the ingredients of the product remain halal,and not in any circumstances applied otherwise.
Keywords: Halal Certification, Protection, Consumer